Avaliação da atividade antimicrobiana da N,N,Ntrimetilquitosana e da quitosana comercial sobre o crescimento de bactérias gram-positivas e gram-negativas e de fungos filamentosos - Silva, Leandro Prezotto da (Universidade Federal de São Carlos, 2014)
Many efforts have been dedicated in the searching of natural compounds which are suitable to be applied in food conservation. Among them, the chitosan has presented promising results concerning the antimicrobial activity, structural preservation and delay of fruits senescence. However, the chitosan, as found commercially, is soluble only in acidic medium solutions what is considered a hindrance for fully applications as food conservative. In this sense, chitosan derivations which are able to be solubilized in neutral pH have been developed. The N,N,N Trimethylchitosan (TMC) is one of them, characterized as a hydrosoluble derivative of chitosan, which has been considered as an efficient antimicrobial agent with positive action as fresh food conservative. The aim of the present was the evaluation of the antimicrobial activity of the TMC against Gram-positive and Gram-negative bacteria and filament fungi. The TMC antimicrobial activity was assessed by comparing with the Commercial Chitosan (CC), by means of the determination of the Minimum Inhibitory Concentration (MIC), following the Clinical and Laboratory Standards Institute (CLSI) according to M7-A6 (NCCLS, 2003) and M38-A (NCCLS, 2002) standards, both recognized by the Agência Nacional de Vigilância Sanitária (ANVISA). Additionally, the TMC and CC antifungal activity was carried out by recoding the visual fungi growth and estimated from the percentage of infected samples by the fungy on cut faces of grape-tomatoes (Solanum lycopersicum variety cerasiforme), in coated and non-coated conditions, along seven days of incubation. The results concerning antibacterial activity points to a greater action of the TMC when comparing to some analysis performed on CC coating against four of the six strains analyzed: Enterococcus faecalis, Staphylococcus aureus, Escherichia coli and Salmonella enterica. Nevetheless the CC antifungal activity was considerable superior to that observed to TMC for three different fungi tested: Penicillium sp., Aspergillus flavus standard and Aspergillus flavus wild. However, both polymers showed high antibacterial and antifungal activity and are therefore considered as natural agents with relevant antimicrobial potential for the fresh food conservation.
Keywords: Alimentos - microbiologia; Agentes antimicrobianos naturais; Concentração inibitória mínima; Alimentos - conservação; Natural antimicrobial agents; Minimum inhibitory concentration; Fresh food conservation; OUTROS